Targeting the stem cell niche micro-environment as therapeutic strategies in aging - Farahzadi, Raheleh; Valipour, Behnaz; Montazersaheb, Soheila; Fathi, Ezzatollah (Frontiers in Cell and Developmental Biology, 2023)
Adult stem cells (ASCs) reside throughout the body and support various tissue. Owing to their self-renewal capacity and differentiation potential, ASCs have the potential to be used in regenerative medicine. Their survival, quiescence, and activation are influenced by specific signals within their microenvironment or niche. In better words, the stem cell function is significantly influenced by various extrinsic signals derived from the niche. The stem cell niche is a complex and dynamic network surrounding stem cells that plays a crucial role in maintaining stemness. Studies on stem cell niche have suggested that aged niche contributes to to the decline in stem cell function. Notably, functional loss of stem cells is highly associated with aging and age-related disorders. The stem cell niche is comprised of complex interactions between multiple cell types. Over the years, essential aspects of the stem cell niche have been revealed, including cell-cell contact, extracellular matrix interaction, soluble signaling factors, and biochemical and biophysical signals. Any alteration in the stem cell niche causes cell damage and affects the regenerative properties of the stem cells. A pristine stem cell niche might be essential for the proper functioning of stem cells and the maintenance of tissue homeostasis. In this regard, niche-targeted interventions may alleviate problems associated with aging in stem cell behavior. The purpose of this perspective is to discuss recent findings in the field of stem cell aging, heterogeneity of stem cell niches, and impact of age-related changes on stem cell behavior. We further focused on how the niche affects stem cells in homeostasis, aging, and the progression of malignant diseases. Finally, we detail the therapeutic strategies for tissue repair, with a particular emphasis on aging.